2016
DOI: 10.1080/01635581.2016.1188971
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Parameters as Risk Factors for Mortality in Cancer Patients

Abstract: The aim of this study was to verify the relationship between weight loss, handgrip strength (HGS) and phase angle (PA) before the beginning of chemotherapy with overall survival in cancer patients. Patients diagnosed with gastrointestinal and breast cancer who were over 18 years old and were scheduled to undergo adjuvant treatment at Hospital Borges da Costa/Brazil were evaluated. The exclusion criteria were neoadjuvant treatment, patients with kidney and liver disease and using diuretics. Weight, HGS and PA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…The association between undernutrition and morbidity and mortality is known and widely documented in the adult population 7,25,26,34,[41][42][43][44][45] ; however, there is a lack of literature that demonstrates this association, evaluated particularly by body composition indicators, in sick and critically ill children. Thus, despite having several limitations, our study reinforces the importance of nutrition assessments in critically ill children and suggests that body composition may be useful not only for nutrition diagnosis and monitoring, but also for an additional indicator in estimating death risk and PICU LOS in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The association between undernutrition and morbidity and mortality is known and widely documented in the adult population 7,25,26,34,[41][42][43][44][45] ; however, there is a lack of literature that demonstrates this association, evaluated particularly by body composition indicators, in sick and critically ill children. Thus, despite having several limitations, our study reinforces the importance of nutrition assessments in critically ill children and suggests that body composition may be useful not only for nutrition diagnosis and monitoring, but also for an additional indicator in estimating death risk and PICU LOS in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, several terms have been used to characterize the nutrition status of an individual, and a call for unanimity has been raised by different experts from nutrition societies . Nonetheless, there is no doubt that unintentional weight loss and decreased food intake, with disease, which may further affect nutrient absorption and utilization, lead to a decline in overall body function, placing the individual at risk of increased morbimortality . Thus, the importance of identifying risk factors for undernutrition (screening) and, when indicated, further assessing the nutrition status (assessment) is fundamental to the best holistic approach of any sick individual.…”
Section: Nutrition Statusmentioning
confidence: 99%
“…45 Nonetheless, there is no doubt that unintentional weight loss and decreased food intake, with disease, which may further affect nutrient absorption and utilization, lead to a decline in overall body function, placing the individual at risk of increased morbimortality. 1,[46][47][48][49] Thus, the importance of identifying risk factors for undernutrition (screening) and, when indicated, further assessing the nutrition status (assessment) is fundamental to the best holistic approach of any sick individual. The disease per se may lead to undernutrition, and undernutrition alone affects disease outcomes in a vicious circle.…”
Section: Nutrition Statusmentioning
confidence: 99%
“…The gender difference in malnutrition effects on mortality is due to the better (baseline) survival in non-malnutrition women than in men, including 95.8 days for women and 35.9 days for men for in-hospital survival, and 299.0 days for women and 268.0 days for men for 1-year survival. One study of malnutrition in patients with cancer reported that gender differences were possibly related to the role of nutritional status in survival 17. But additional larger studies may be required to further examine the gender differences of malnutrition on survival in critically ill patients with acute renal failure.…”
Section: Discussionmentioning
confidence: 99%